Trajectories and typologies of pre-sentence restorative justice rituals$d - Rossner, Meredith (The Australian and New Zealand journal of criminology, 2018)
Enthusiasm for restorative justice has seen conferencing brought in to the mainstream of criminal justice systems around the world. This raises concerns over how integration into criminal justice will impact conference dynamics. In this article, we present new findings from a study of restorative justice conferences at the pre-sentencing stage for adult offenders. By documenting the interactional dynamics of conferences it reveals the emotional trajectories that conferences take, and the factors that shape immediate conference outcomes. Our results show both the positive aspects of what restorative justice is capable of achieving as well as the tensions that arise when it is integrated within conventional criminal justice. We offer a refined vision of what success can mean in restorative justice at the pre-sentence stage.